A Single Education Session of Orthopaedic Residents Does Not Reduce The Rate of Failed Nonoperative Management or Improve Radiographic Outcomes in Pediatric Distal Radius Fractures. (October 2020) - Compton, Edward; Lin, Adrian; Illingworth, Kenneth D.; Bent, Melissa A.
Abstract : Introduction: The primary objective was to evaluate whether a single educational session on casting is sufficient to reduce the rate of loss of reduction in pediatric distal radius fractures. Methods: A retrospective review was conducted of pediatric patients with distal radius fractures casted between November 2016 and February 2019. Patients were divided into two groups: those casted by a resident who participated in a targeted education session on short arm casting and those who had not. Results: A total of 137 patients were included (education cohort: 61 patients and noneducation cohort: 76 patients). The two groups demonstrated similar ages and pre/post-reduction radiographic measurements. In the education cohort, 11.5% required repeat casting, wedging, or surgical intervention versus 17.1% of patients in the noneducation cohort ( P = 0.47). Patients casted by residents doing one of their first three independent casts trended toward being more likely to place a cast with poor cast index and to lose reduction ( P = 0.12 and P = 0.43, respectively). Discussion: A one hour education session did not reduce the need for intervention or loss of reduction. For educating residents on the skill of casting to be effective, one may consider formal feedback and evaluation throughout multiple education sessions and in early episodes of clinical care. Level of Evidence: A Level III, Retrospective Comparative Study